EDUKASI MASYARAKAT TENTANG KEAMANAN SIBER DALAM TANTANGAN DAN SOLUSI DI ERA DIGITAL - Wijaya, Rama; Juardi, Didi (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
The advancement of digital technology has brought convenience to many aspects of life but also increased cybersecurity threats. This study aims to analyze the main challenges in cybersecurity education in Indonesia and propose inclusive and adaptive solutions for communities with diverse levels of digital literacy. A qualitative research method with document analysis was employed, using data from government reports, national surveys, academic articles, and online news. The findings reveal that low public awareness, digital access inequality, and suboptimal policy coordination are the main obstacles to achieving national cybersecurity resilience. Community-based education and low-tech media such as pamphlets and direct training have proven effective in improving digital literacy by up to 60% in low-infrastructure areas. The study recommends three strategic actions: enhancing inclusive digital literacy, establishing an independent data protection authority, and fostering cross-sector collaboration to strengthen national cybersecurity resilience.